The relationship between proteinuria and allograft survival in patients with transplant glomerulopathy: a retrospective single‐center cohort study. (6th December 2020) - Zhang, Qiang; Rudolph, Birgit; Choi, Mira; Bachmann, Friederike; Schmidt, Danilo; Duerr, Michael; Naik, Marcel G.; Duettmann, Wiebke; Schrezenmeier, Eva; Mayrdorfer, Manuel; Halleck, Fabian; Wu, Kaiyin; et al.
Summary: Proteinuria and transplant glomerulopathy (TG) are common in kidney transplantation. To date, there is limited knowledge regarding proteinuria in different types of TG and its relationship to allograft survival. A retrospective cohort analysis of TG patients from indication biopsies was performed to investigate the relationship of proteinuria, histology, and graft survival. One hundred and seven (57.5%) out of 186 TG patients lost their grafts with a median survival of 14 [95% confidence interval (CI) 10–22] months after diagnosis. Proteinuria ≥1 g/24 h at the time of biopsy was detected in 87 patients (46.8%) and the median of proteinuria was 0.89 (range 0.05–6.90) g/24 h. TG patients with proteinuria ≥1 g/24 h had worse 5‐year graft survival (29.9% vs. 53.5%, P = 0.001) compared with proteinuria <1 g/24 h. Proteinuria was associated with graft loss in univariable Cox regression [hazard ratio (HR) 1.25, 95% CI, 1.11–1.41, P < 0.001], and in multivariable analysis (adjusted HR 1.26, 95% CI 1.11–1.42, P < 0.001) independent of other risk factors including creatinine at biopsy, positive C4d, history of rejection, and Banff lesion score mesangial matrix expansion. In this cohort of TG patients, proteinuria at indication biopsy is common and associated with a higher proportion of graft loss.